(untitled) (Research, Society and Development, 2022)
Introduction: For the development of any human being to happen in a healthy way, there are internal factors that are genetic and external factors that are related to family, cultural, and socioeconomic eating habits; where food is the basis for human development and has its repercussions throughout the individual’s existence. Objective: To describe the influence of healthy eating in the phase of food introduction. Methodology: This is a literature review with a descriptive approach. Results: From the literature study it was possible to observe the importance of one of good eating habits and that these if taken correctly at all stages of life, can favor a better quality of life for any individual. Discussion of the results: The importance of breastfeeding was presented, the most common methods used in the introduction of food after 6 months the effective correlation of the influence of family and school in the child’s food choices, as well as the prevention of possible diseases. Conclusion: We can conclude that a healthy and balanced diet, with adequate consumption of fruits, vegetables, and nutrient-rich foods, from the beginning of the child’s introduction to food, will develop healthy habits that can be taken for life.